(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The increasing incidence of urban fire emergencies in Manila City emphasizes the need for efficient, technology-driven response systems capable of improving situational awareness and communication. Conventional fire reporting methods, which rely primarily on manual calls and delayed verification, often result in slower response times and limited coordination among emergency responders. This study aimed to develop and evaluate the Smart Application for Emergency Response (S.A.F.E.R.), an Android-based mobile application designed to enhance fire emergency preparedness and response through real-time location tracking, rapid incident reporting, safety guidance alerts, direct communication channels, and community resilience tools. A descriptive research design was employed, supported by an agile iterative development methodology. The system was evaluated using the Mobile App Rating Scale (MARS) for user-based assessment and the ISO/IEC 25010 software quality model for technical evaluation. A total of 56 respondents participated in the study, comprising 50 Manila City residents and 6 IT/subject matter experts. Descriptive statistical techniques, including mean and standard deviation, were used to analyze the collected data. Evaluation results showed that